2017
DOI: 10.1186/s40172-017-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term consequences of pollution on labor supply: evidence from Indonesia

Abstract: We use a natural experiment in Indonesia to study the medium-and long-term effects of air pollution on labor supply. We find that exposure to air pollution reduces hours worked and while the medium-term effects are larger in magnitude, some effects do persist in the long term. More interestingly, we are able to provide some insight regarding the underlying channels that contribute to the reduced labor supply. Own health seems to be the only responsible channel in the long term, while in the medium term, a diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 34 publications
4
27
1
3
Order By: Relevance
“…Aside from damaging the health of laborers themselves, the long-term exposure to severe air pollution may also compel the adult laborers to spend more time caring for infected children and elders, thereby resulting in an increased absenteeism and shortened working hours. Kim et al [24] studied the medium-and long-term effects of air pollution on labor supply based on a natural experiment of the 1997 Indonesian forest fires. They found that the exposure to air pollution shortened the working hours of laborers, and that the parents with children were more prone to working hour reductions during severe pollution incidents.…”
Section: Air Pollution and Loss Of Labor Supplymentioning
confidence: 99%
“…Aside from damaging the health of laborers themselves, the long-term exposure to severe air pollution may also compel the adult laborers to spend more time caring for infected children and elders, thereby resulting in an increased absenteeism and shortened working hours. Kim et al [24] studied the medium-and long-term effects of air pollution on labor supply based on a natural experiment of the 1997 Indonesian forest fires. They found that the exposure to air pollution shortened the working hours of laborers, and that the parents with children were more prone to working hour reductions during severe pollution incidents.…”
Section: Air Pollution and Loss Of Labor Supplymentioning
confidence: 99%
“…Air pollution thus increases gender inequality in the labour market (Montt, 2018). The health effects of intense air pollution persist in the long term, even ten years after exposure (Kim, Manley and Radoias, 2017). Taking into account only premature deaths, air pollution costs the world economy about US$ 225 billion in lost labour income and US$ 5 trillion in welfare losses.…”
Section: Overexploitation Of Fish Stocks Could Destroy 857 Million Jobsmentioning
confidence: 99%
“…Extensive evidence links weather and pollution to health outcomes (Deschênes et al , 2009), and recent studies link pollution (Allen et al , 2017), temperature (Graff Zivin et al , 2018) and precipitation (Maccini and Yang, 2009) to cognition and schooling. The effects of temperature and precipitation on labor market outcomes have been extensively examined (Dell et al , 2014), and there is also evidence that pollution impacts labor market outcomes (Kim et al , 2017). While the long-term human capital effects of weather have been explored (Graff Zivin and Neidell, 2013), few studies have examined the long-term human capital effects of early-life pollution exposure (Currie et al , 2014), with fewer making the link to labor market outcomes (Kim et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of temperature and precipitation on labor market outcomes have been extensively examined (Dell et al , 2014), and there is also evidence that pollution impacts labor market outcomes (Kim et al , 2017). While the long-term human capital effects of weather have been explored (Graff Zivin and Neidell, 2013), few studies have examined the long-term human capital effects of early-life pollution exposure (Currie et al , 2014), with fewer making the link to labor market outcomes (Kim et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation